PENGEMBANGAN PRODUKSI CABAI MERAH MELALUI PENDEKATAN STANDAR OPERASIONAL PROSEDUR PADA MUSIM KEMARAU DI LAHAN KERING KABUPATEN BLORA - Endang Iriani; M Eti Wulanjari (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
Agricultural innovation less useful if not disseminated and applied to the development of agribusiness by the perpetrators. Today has been a lot of agricultural innovations, especially those that are the result of research and development AARD is ready to be applied in order to develop agribusiness system. Chili farming has significant economic value because of the production, pricing and market opportunity is quite flutuatif. Blora District in particular regions is one of the District Jepon chili production centers, except for the location of assistance activities in the Village Jepon chilli farming peasants who still undeveloped, so that in efforts to increase business and technology skills necessary assistance. The objective is to develop an approach to the production of chili through Standard Operating Procedures (SOP). Assistance activities chili farming technology through the application of SOP approach in the dry season in dry land area of ​​1 hectare Blora District conducted in July-November 2009, by applying cultivation technology in order to optimize production and farmers' income. The results obtained in general the development of farm chili dry season (DS) in the Village Jepon average production is still below the potential yield. This is because of environmental stress the limited availability of water, resulting in inadequate crop farmers must use kocoran. However, these results still provide benefit financially supported due to higher prices. These conditions have motivated farmers around the site to develop in the rainy season of 2009-2010. Development of chilli farming in the next planting season (RS) of 1.2 acres held by 11 farmers covering an average of 0.1 hectares per person growers with good results.